COOH-terminal sequence of the cellular prion protein directs subcellular trafficking and controls conversion into the scrapie isoform - Kaneko, Kiyotoshi (The National Academy of Sciences of the USA, 1997)
Efficient formation of scrapie isoform of prion protein (PrP(Sc)) requires targeting PrP(Sc) by glycophosphatidyl inositol (GPI) anchors to caveolae-like domains (CLDs). Redirecting the cellular isoform of prion protein (PrP(C)) to clathrin-coated pits by creating chimeric PrP molecules with four different COOH-terminal transmembrane domains prevented the formation of PrP(Sc). To determine if these COOH-terminal transmembrane segments prevented PrP(C) from refolding into PrP(Sc) by altering the structure of the polypeptide, we fused the 28-aa COOH termini from the Qa protein. Two COOH-terminal Qa segments differing by a single residue direct the transmembrane protein to clathrin-coated pits or the GPI form to CLDs; PrP(Sc) was formed from GPI-anchored PrP(C) but not from transmembrane PrP(C). Our findings argue that PrP(Sc) formation is restricted to a specific subcellular compartment and as such, it is likely to involve auxiliary macromolecules found within CLDs.